Kepemimpinan Organisasi Pembelajaran Program Studi Bahasa Inggris di STKIP PGRI Ngawi - Susilowati, Nuri; Suyatmini, Suyatmini (Muhammadiyah University Press, 2016)
The research Â hasÂ five proposed: 1) to describe personal mastery of leadership in english departement at STKIP PGRI Ngawi, 2) to desribe mental methods of leadership in english departement at STKIP PGRI Ngawi, 3) to describe shared vision of leadership in english departement at STKIP PGRI Ngawi, 4) to describe system thinking of leadership in english departement at STKIP PGRI Ngawi. 5) to describe team learning of leadership in english departement at STKIP PGRI Ngawi. The skill is descripÆve qualitaÆve research; study case. The source of the data research from the chairman, lecture and students. The result of the research shows that are: 1) personal mastery: a) commitment; personal and a shared commitment, b) creativity, innovative and priorities; good creativity, innovative and priorities. 2) mental methods: a) criticism and suggestions; received and evaluated of the criticism and suggestions, b) Behavior;Â Â discipline, responsible and friendly. 3) Shared vision: a) motivation and oppeness; good motivation and slightly open, b) Vision; shared vision. 4) systems thinking has not been so appears. 5) Tim learning: a) position; the position isnât an obstacle to maintain good relations between the others, b) dialogue and discussion; to improve communication.